Modelling capability-based risk assessment for international construction project ventures / Loo Siaw Chuing - Loo, Siaw Chuing (2015)
Globalization has created more opportunities for contractors to enter international construction markets. Despite the financial markets meltdown in the autumn of 2008, international contractors are still finding opportunities in the international marketplace. International projects are exposed to more diverse and complex risks, thus higher possibility of loss, than domestic projects. Similarly, the vast uncertainties and complexities in international construction would render project selection decisions to be intricate as compared to domestic construction. As a result, copious risk assessment tools and methods have been proposed to assist this decision making, most of them based on Probability-Impact (P-I) risk model. Although P-I risk model is useful to assess risks, firm’s capabilities are missing in the early assessment to provide accurate risk picture to decision makers for project selection decision in the international construction. This study aims to develop a risk assessment model, through the determination of the extent to which firm’s capabilities impact on international construction project risk significance values, for improved productivity and performance. The international construction firm’s capabilities are explored using resource-based view, dynamic capabilities, and Porter’s generic value chain theories. The conceptual framework postulated that international construction firms could lower the exposure to risks in the international construction foray by a combination of firm’s capabilities. A total of 252 survey questionnaires were sent out in 2013 to 2014 to 155 international construction firms and 65 firms responded via either structured interview or questionnaire survey. The respondents are project selection decision makers in their firms and thus are approached through face-to-face interviews if they are based in Malaysia or contacted via email if they are based in their home countries. The data collected were analyzed using SPSS and PLS-SEM software. The results from structural iv model evaluation found that only 53 out of 110 hypothesized relationships were significantly important. It was discovered that four firm’s capabilities have less influence on the risks studied; they are financial, innovation, physical, and procurement capabilities. This suggests that human resource, organizational, business management, organizational learning, construction, and project management capabilities are more influential towards international construction risk significances. A novel Capability- Risk Assessment (CapRA) model was developed and validated using the PLS-SEM technique. The model was then formulated into modified P-I risk model equations and computerized into a CapRA calculator to facilitate construction firms in selecting international construction projects. The Mean Absolute Percentage Error found that CapRA is able to improve prediction accuracy by 16% to 21%. International contractors are recommended to use CapRA to conduct preliminary assessment on their firm’s capabilities and risks of potential projects. This study contributes to the knowledge of risk assessment by enhancing the P-I risk model with firm’s capability component. The model developed enables firms to be informed of the combination of firm’s capabilities needed to lower the exposure to certain risks. Thus, a proper assessment of firm’s capabilities and project risks before coming into any decision can be achieved. Future study could incorporate other influencing variables such as various contract clauses to refine CapRA.